Analisis Kehidupan Efektif Sehari-Hari Guru Bimbingan Konseling SMA Negeri Se-Kota Padang - Theresia Riannita Sijabat; Yarmis Syukur (YASIN, 2026)
Effective daily life among guidance and counseling teachers/counselors is an important factor in improving the quality of guidance and counseling services in schools, because teachers who are able to manage their everyday lives in a directed, productive, and meaningful manner are expected to be more optimal in supporting students’ development. This study aimed to analyze the effective daily life of guidance and counseling teachers/counselors at Public Senior High Schools in Padang City, examined across five aspects: (1) concrete and positive goals; (2) implementation that is effective, efficient, and enjoyable; (3) outcomes that are satisfying and developmental; (4) benefits that are aligned with positive and productive life goals; and (5) contextualization that is positive and accommodative. This study employed a quantitative approach with a descriptive research design. The population comprised all 86 guidance and counseling teachers/counselors at Public Senior High Schools in Padang City, who simultaneously served as the research sample through a total sampling technique. Data were collected using the Effective Daily Life Scale based on a Likert model and analyzed with the assistance of Microsoft Excel and SPSS 25.0 for Windows. The results showed that, overall, the effective daily life of guidance and counseling teachers/counselors at Public Senior High Schools in Padang City was in the very good category, with a percentage of 80.28%. These findings indicate that, in general, guidance and counseling teachers/counselors have been living effective daily lives, which has positive implications for the implementation of guidance and counseling services in Public Senior High Schools in Padang City.